Analisis Deskriptif Implementasi Hospitality Mindset dalam Layanan Front Office di Politeknik NSC Surabaya - Zerlina Nathania; Siti Mahmudah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Front office services at vocational education institutions significantly influence institutional image and student satisfaction. This study aims to describe the implementation of the hospitality mindset within the front office services at Politeknik NSC Surabaya based on perceptions from students across five academic programs. A descriptive qualitative approach was employed, supported by quantitative data from questionnaires and participatory observations. The questionnaire utilized the SERVQUAL dimensions—tangibles, reliability, responsiveness, assurance, and empathy—and data were analyzed using SPSS 25. The analysis involved descriptive statistics from 99 valid respondents. Results indicate high scores across all dimensions, with assurance achieving the highest rating (3.85) and empathy the lowest (3.70). The findings suggest strong professionalism and trustworthiness among front office staff, although personal attention and empathy require enhancement. This research broadens the implementation of the hospitality mindset into educational administrative services, emphasizing empathy and responsibility as crucial elements for student satisfaction. Practical implications include recommendations for targeted staff training and operational procedure improvements in institutional services.